THE DEVELOPMENT OF A MODEL SYSTEM FOR THE CHARACTERIZATION OF CANCER STEM CELL PROPERTIES IN BRAIN METASTASES FROM THE LUNG - Nolte, Sara M. (My University, 2012)
Brain metastases are most common in adults suffering from lung cancer, predicting uniformly poor patient outcome and short survival time. Despite their frequency and severity, very little is known about the tumorigenesis of brain metastases. Previously developed primary brain tumour-initiating cell (BTIC) models were used to determine the presence of a stem-like population in brain metastases from the lung. Use of clinical samples and the NCI-H1915 cell line allowed for the development of useful strategies for study of brain metastasis.
The sphere formation capacity and expression of known BTIC markers in brain metastases was suggestive of a self-renewing population. Differentiation studies demonstrated that neither clinical samples nor NCI-H1915 cells had neural lineage potential. Intracranial xenotransplant of clinical samples and NCI-H1915 cells into NOD-SCID mice led to formation of multiple focal masses throughout the ventricles; the tumours were also serially transplantable, further implicating a TIC population. Of known BTIC markers, only CD15 expression levels and patterns were similar enough in clinical samples and NCI-H1915 cells to warrant prospective sorting experiments in the cell line. Use of CD15 failed to identify a CSC or TIC population in NCI-H1915 cells.
These findings suggest that a TIC population is present in brain metastases; however, this remains to be identified. It is recommended that due to the limitations of cell surface markers, the study of brain metastasis should use a selective gene expression approach, in order to target genes and pathways essential to metastasis. It was shown that NCI-H1915 cells could be useful for such an approach, studying the effects on proliferation, sphere formation, and tumour formation capacity of brain metastases from the lung. Further study using this model could ultimately lead to the disruption of pathways essential to the metastatic process, transforming a uniformly fatal disease into a more localized and treatable one.
Keywords: brain metastasis; metastatic lung cancer; cancer stem cell; tumour-initiating cell; Cancer Biology; Cancer Biology